Financialisation and inequality in the semi-periphery: Evidence from Portugal - Lagoa, S.; Barradas, R. (Financialisation in the European periphery: Work and social reproduction in Portugal, 2020)
Despite being a disputed concept in the literature, financialisation broadly refers to the growing weight of finance in modern economies. This chapter looks at how the evolution of inequality in Portugal is related to financialisation. It analyses functional income distribution, looking at the wage share and rentier income. The chapter focuses on personal income distribution and poverty. It approaches briefly other effects of financialisation and other factors explaining functional and personal income inequality and poverty. Wage inequality is relevant to analyse the distribution of income before state intervention with taxes and social policies. When analysing income inequality, the focus is on relative differences between households, without concern for poverty, that is, for the incapacity of some households for having a minimum income that ensures an ordinary living pattern. In conclusion, the Portuguese experience shows that the financialisation process has some direct and indirect effects on income inequality.